Synthesis of Hierarchical TiO2–C3N4 Hybrid Microspheres with Enhanced Photocatalytic and Photovoltaic Activities by Maximizing the Synergistic Effect. Issue 1 (10th November 2016) - Wang, Wei; Liu, Yu; Qu, Jifa; Chen, Yubo; Tadé, Moses O.; Shao, Zongping
Abstract: To maximize the synergistic effect between the components in a TiO2 –C3 N4 hybrid, strongly heterostructured three‐dimensional (3D) porous TiO2 –C3 N4 microspheres with a hierarchical nano/microstructure are developed by a solvothermal method and used as photocatalysts for organic waste degradation and as photoanodes for dye‐sensitized solar cells (DSSCs), showing superior photoactivity. The rich heterojunctions and strong interfacial connections between TiO2 and C3 N4 greatly improve the separation efficiency of the photogenerated electron–hole pairs. This hybrid exhibits superior photocatalytic activity compared to TiO2 –C3 N4 composites prepared by traditional physical mixing and reported post‐synthesis methods. A DSSC prepared with this hybrid as the photoanode displays superior or comparable photoelectric efficiency to those of the best reported photoanodes. A possible mechanism for the improved photoactivity of this hybrid is proposed. This strongly heterostructured TiO2 –C3 N4 hierarchical microspherical material is expected to provide a good foundation for the design and synthesis of advanced materials for photocatalytic and photovoltaic applications. Abstract : Let′s collaborate ! To maximize the synergistic effect between the components in a C3 N4 –TiO2 hybrid, strongly heterostructured 3D porous TiO2 –C3 N4 microspheres with rich heterojunctions are developed as photocatalysts to degrade organic substances and as photoanodes for dye‐sensitized solar cells. This hybrid exhibits superior photocatalytic activity compared to TiO2 –C3 N4 composites prepared by traditional physical mixing and post‐synthesis methods.